Mass Spectrometry as an Efficient Tool for the Characterization of Amyloid β Peptide 25–35 Self-Assembly Species in Aggregation and Inhibition Studies. Issue 6 (December 2013) - Fiori, J.; Naldi, M.; Andrisano, V.
Amyloid beta 25–35 [Aβ (25–35)], as a peptide model for full-length Aβ in structural and functional investigations, has been chosen for aggregation studies. The complexity of the Aβ (25–35) aggregation process required a multi-methodological analytical approach to obtain reliable and reproducible results. Here, we describe the results obtained by the use of mass spectrometry (MS) for the structural characterization of the self-assembly species during the aggregation process and for the definition of the self-assembly kinetics and myricetin inhibition patterns, comparing the results with those obtained by using the well-established spectroscopic method based on thioflavin T fluorescence. Flow injection electrospray ionization-ion trap-mass spectrometry (ESI-IT-MS) was applied to monitor the disappearance of the monomer specie in the first steps, whereas matrix-assisted laser desorption/ionization-time of flight-mass spectrometry (MALDI-ToF-MS) was used to follow monomer and small oligomer self-assembly trends in the early stages of the nucleating process.